The effect of the MyBFF@school program on cardiorespiratory fitness in overweight and obese primary schoolchildren: a cluster randomized controlled trial - Abdul Halim Mokhtar; Muhammad Ashaari Kamarudin; Alston Choong; Lakvinder Singh; Vinotha Genisan; Abqariyah Yahya; Ruziana Mona Wan Mohd Zin; Fuziah Md. Zain; Rusidah Selamat; Zahari Ishak; Muhammad Yazid Jalaludin (BMC Public Health)
Abstract Background MyBFF@school program consisting physical activity in the formed small-sided games (SSG), nutrition and psychology education was designed to combat obesity among schoolchildren in Malaysia. It was expected to improve cardiorespiratory fitness, hence, contributing to obesity treatment and prevention. Thus, we aimed to study the effects of the MyBFF@school program on the cardiorespiratory fitness of overweight and obese primary schoolchildren. Methods Twenty-three out of 1196 government primary schools in central Peninsular Malaysia participated in this cluster-randomized control study. Schoolchildren aged 9–11 years with a body mass index (BMI) z-score greater than + 1 SD (WHO) were eligible for the study. The intervention group participated in the MyBFF@school program while the control followed the existing standard curriculum. The primary outcome was cardiorespiratory fitness using physical fitness score (PFS) measured by the modified Harvard step test. Data were collected at baseline, month-3 and month-6 and were analyzed according to the intention-to-treat principle using mixed linear models. Results A total of 954 schoolchildren completed six months follow up, with 439 (n = 439) in the intervention group (n = seven schools), while 515 (n = 515) in the control group (n = 16 schools). In the first three months, there was significant within-group PFS improvement in overall (both), girls (both) and obese (control). Comparing between-groups, the mean differences favored the control in most parameters, but were not significant: overall (-0.15(-0.75, 0.45), p = 0.83), boys (-0.07(-0.98, 0.83), p = 0.83), girls (-0.27(-1.27, 0.73), p = 0.81), overweight (-0.16(-1.28, 0.94), p = 0.97), obese (-0.05(-1.03, 0.92), p = 0.93), morbidly obese (-0.68(-2.43, 1.05), p = 0.26), urban (0.07(-0.79, 0.94), p = 0.45), and rural (-0.35(-1.34, 0.62), p = 0.30). At month-six, the within-group improvements maintained. However, the mean differences now favored the intervention group although they remained not significant: overall (0.05(-0.98, 1.07), p = 0.69), boys (0.06(-1.35, 1.46), p = 0.86), girls (0.10(-1.31, 1.51), p = 0.74), overweight (0.15(-1.07, 1.36), p = 0.93), obese (0.28(-0.98, 1.55), p = 0.75), morbidly obese (-0.79(-2.74, 1.15), p = 0.47), urban (0.61(-0.56, 1.77), p = 0.47), and rural (-0.69(-2.52, 1.14), p = 0.17). Conclusions MyBFF@school program showed positive trend in cardiorespiratory fitness changes especially after six months. MyBFF@school intervention program has the potential to combat obesity in primary schoolchildren and should be at least six months. Trial registration Clinical trial number: NCT04155255, November 7, 2019 (Retrospective registered). National Medical Research Register: NMRR-13-439-16563. Registered July 23, 2013. The intervention program was approved by the Medical Research and Ethics Committee (MREC), Ministry of Health, Malaysia and, the Educational Planning and Research Division (EPRD), Ministry of Education, Malaysia. It was funded by the Ministry of Health, Malaysia.